opagenumbers CD_4^ + CD_25^ + Treg cells in thrombotic thrombocytopenic purpura associated with systemic lupus erythematosus patients. (September 2014) - Huang, Hongdong; Sun, Weiming; Liang, Yumei; Long, Xi-Dai; Peng, Youming; Liu, Zhihua; Wen, Xiaojun; Jia, Meng
Abstract Aim: <![CDATA[ opagenumbers CD_4^+ CD_25^ + ]]> Treg cells are of critical importance for maintenance of tolerance. The purpose of the this study was to observe the number of <![CDATA[ opagenumbers CD_4^+ CD_25^ + ]]> Treg cells in the patients with thrombotic thrombocytopenic purpura (TTP) associated with systemic lupus erythematosus (SLE), and to study pathogenesis of TTP with SLE. Methods: Seven patients with TTP associated with SLE and seven healthy volunteers were studied. The <![CDATA[ opagenumbers CD_4^+ CD_25^ + ]]> Treg cells were examined by flow cytometry. Clinical and laboratory data, such as urinary protein, serum creatinine, endothelial markers and immunologic serologics, were obtained from each patient and healthy volunteer. Glomerular injury was assessed by histopathology. Serum IL-2, IL-4, IL-6 and anti-endothelial cell antibody were analyzed by ELISA and anti-ADAMTS13 antibody were detected by Western blotting. Results: <![CDATA[ opagenumbers CD_4^+ CD_25^ + ]]> Treg cells significantly decreased in TTP with SLE patients compared with controls (p < 0.05). <![CDATA[ opagenumbers CD_4^+ CD_25^ + ]]> Treg cells are negatively correlated with blood urea nitrogen, serum uric acid, supernatant IL-4, and proteinuria, and positively with estimated glomerular filtration rate (eGFR) in TTP with SLE patients. <![CDATA[ opagenumbers CD_4^+ CD_25^ + ]]> Treg cells gradually decreased as the severity of renal histology increased. Serum IL-2, IL-6, supernatant IL-4, anti-endothelial cell antibody, and anti-ADAMTS13 antibody significantly increased in TTP with SLE patients compared to those of the control groups (all p < 0.05). In contrast, serum levels of C3 were significantly decreased in TTP with SLE patients compared to those of the control groups (p < 0.05). Conclusions: <![CDATA[ opagenumbers CD_4^+ CD_25^ + ]]> Treg cells are not only lower in TTP with SLE patients, but also are correlated with disease severity in TTP with SLE patients. <![CDATA[ opagenumbers CD_4^+ CD_25^ + ]]> Treg cells may play an important role in the pathogenesis of TTP with SLE.